Calculation of energy transaction allocation factors. - Fradi, A. (IEEE Transactions on power systems)
The ability to allocate the MW loading on transmission lines and groups of lines is the basis of NERCs ?flow based? transmission allocation system. In such a system, the MW flows must be allocated to each line or group of lines in proportion to the MWs being transmitted by each transaction. This is accomplished through the use of the linear power transfer distribution factors. Unfortunately, no linear allocation models exist for other transmission phenomena such as MW losses, MVA flows, etc. This paper presents a methodology to calculate energy transaction allocation factors (ETA Factors, or η factors), using the well-known process of integration of a first derivative function. The factors give a highly accurate allocation of any nonlinear transmission system quantity to the active transactions placed on a transmission system